Site index - The Editors, - (Nordic Archaeological Abstracts - NAA, 1978)
The specific names of sites are listed only for castles, churches, towns, and wellknown find localities. The name of the relevant county, district, or region according to the map is listed. If a paper· deals with a larger area this is not included. For the area outside the Nordic the name of the country is listed as are well-known find localities.